Analysis Of Work Culture And Compensation To Improve Teacher Performance (Case Study At Paud Puri Mulya) - Sri Ratna Ningsih; Budi Rismayadi; Neni Sumarni (Trigin Publisher, 2022)
The purpose of this study is to determine work culture and compensation in improving performance so that it has good performance. This study uses a qualitative method with the techniques used are method triangulation techniques, data triangulation techniques and theory or reference triangulation techniques. Based on the results of the study, it was found that the work culture that existed at Puri Mulya PAUD was seen from the cultural instrument between co-workers that was well established, but the compensation given was not appropriate, and there was no bonus given if in PAUD, salary payments were still delayed, but performance teachers can still be assessed as very good because the dedication of the teacher's role as educators is very high